Wearable doorbell notification for deaf people / Hafiqa Eliya Haliza - Haliza, Hafiqa Eliya (2019)
Wearable Doorbell Notification for Deaf People is a wearable device to alert the deaf people who supposed to be the wearer of the device whenever there are people pressed their doorbell by using the wireless technology, nRF24L01 wireless module and Arduino Nano to produce the device with additional components such as push button, LED, LCD and vibrating motor. Most deaf people were using light doorbell notification that was placed in certain room. This situation caused them to not be alert of the light doorbell notification if they stay in another room because of mobility issue. The project objective includes the development of the wearable doorbell notification and evaluation of its reliability based on its functionality and network performance. There is two types of experiments were conducted in this project, functionality test and network performance test. These experiments have been divided into a few parts. The results shows that the higher the RF power amplifier used by nRF24L01, the higher the distance that can be reached by a signal from the doorbell to the wearable. It also shows that the data transmission rate did not influenced the response time of the wearable. The recommendations for future research were to fix the problems in the wearable and create a wearable alert device with more alarms such as baby crying alarm, fire alarm and vulgar alarm.